2019
DOI: 10.3390/ma12081321
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Specific Energy Density on Microstructure and Corrosion Resistance of CoCrMo Alloy Fabricated by Laser Metal Deposition

Abstract: With the development of modern medical implants, there are significantly increasing demands for personalized prosthesis. Corrosion-resistance and dense cobalt alloy specimens have been successfully fabricated by laser metal deposition. The relationship between specific energy density, microstructure and corrosion resistance of the specimens is investigated. The results show that higher specific energy density promotes the formation of columnar grain and leads to coarse grain size. The evolution and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although both the prepared 3D-printed alloy and the purchased cast alloy satisfied the chemical composition given by the ASTM F75 standard, we analyzed a low amount of C in the 3D-printed material compared to the cast material. Some works in which C was present [33,50,52] reported the presence of carbide precipitates in the intercellular network instead of Mo segregation on dislocation walls or σ precipitates that we observed.…”
Section: Initial Microstructurementioning
confidence: 42%
“…Although both the prepared 3D-printed alloy and the purchased cast alloy satisfied the chemical composition given by the ASTM F75 standard, we analyzed a low amount of C in the 3D-printed material compared to the cast material. Some works in which C was present [33,50,52] reported the presence of carbide precipitates in the intercellular network instead of Mo segregation on dislocation walls or σ precipitates that we observed.…”
Section: Initial Microstructurementioning
confidence: 42%
“…67 During the LPBF AM process, the XZ plane is (re)heated more than the XY plane. 68 The XY plane, being more rapidly cooled, therefore, may show less ε-phase, while the XZ plane is more similar to wrought CoCrMo. This behavior is more pronounced on the surface; a previous study on polished and unpolished LPBF-XY samples showed no ε-phase for the unpolished (and more rapidly cooled) surface than the polished surface underneath.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the γ-phase is not thermodynamically stable and can be transformed into the ε-phase during cooling . During the LPBF AM process, the XZ plane is (re)­heated more than the XY plane . The XY plane, being more rapidly cooled, therefore, may show less ε-phase, while the XZ plane is more similar to wrought CoCrMo.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the lifespan of the existing valves, we employed LPBF technology to deposit a 5 mm thick CoCrMo layer onto the base of an IN625 (Inconel625) valve core. This will significantly enhance their durability and performance in corrosive environments [10][11][12]. Therefore, this technology represents a significant advancement in safeguarding the integrity of petrochemical processes and reducing the economic risks associated with corrosion-related failures [13][14][15].…”
Section: Introductionmentioning
confidence: 99%